(untitled) (Journal of Geography and Environmental Management, 2022)
The article presents the results of work to determine the trend in the flow of the rivers Zhem, Oiyl and results of expeditions to the regions of the river location, conducted in 2021 to assess the ecological state of the river basins under the guidance of a working group of scientistsWater specialists of the Ministry of Ecology, Geology and Natural Resources (MEGCR). The main aim of the work is to assess the trends in the flow of the Zhem and Oiyl rivers. In order to solve these problems, the dynamics of changes in the main meteorological factors that determine the formation of river flow in the region under consideration are considered: the sum of precipitation for the winter period, autumn soil humidification, average annual air temperature and anthropogenic influence on river flow. Genetic analysis of the assessment of changes in flow since the 1950s revealed a disturbance in flow caused by economic activity with the introduction of a dam system in the river basins for estuarine irrigation. On the basis of the above-mentioned studies, the assessment of changes in the flow of the Zhem and Oiyl rivers was carried out respectively by differentiating the mean long-term values of the flow of the conditional-natural period (1935-1950) with the run-off of the period of influence of economic activity (1951-1975) and the period of influence of economic activity in conjunction with the change of climatic factors (1976-2019). It was found that during the combined period of economic activity and changes in climatic factors, compared to the conventional period, the flow of the River Zhem decreased by 49 %, the flow of the river Oiyl by 26 %.